Savidu 2016 - Volume 02 Issue 01 - (:unkn) unknown (My University, 2016)
Savidu-University Newsletter: 2016 - Volume 02 Issue 01 has now been published, showcasing the vibrant academic, cultural, and communal life of the esteemed University of Sri Jayewardenepura (USJ). This online publication captures the essence of our dynamic institution through a wealth of engaging articles, captivating stories, and insightful interviews that reflect the rich tapestry of experiences and achievements within the university community. It further invites readers to embark on a journey of knowledge, creativity, and collaboration, highlighting the remarkable endeavors of USJ and its exceptional individuals.